The Burden of Diabetes-Related Chronic Kidney Disease in China From 1990 to 2019 - Pan, Xiaowen; Lin, Xiling; Huang, Xin; Xu, Jingya; Ye, Lingxia; Zhang, Tianyue; Hu, Shaoning; Jiang, Hongwei; Ren, Yuezhong; Shan, Peng-Fei (Frontiers in Endocrinology, 2022)
Objective To analyze the trends in disease burden of diabetes-related chronic kidney disease (CKD) by year, age, gender and types of diabetes in China from 1990 to 2019. Methods Data on prevalence, deaths and disability-adjusted life years (DALYs) for diabetes-related CKD were extracted from the Global Burden of Disease (GBD) 2019 study. Analyses were performed by year, age, gender and types of diabetes. Results In China, the numbers of deaths and DALYs of diabetes-related CKD continuously increased but the age-standardized rates (per 100,000 population) decreased over 30 years, in which the numbers of deaths and DALYs attributable to type 1 diabetes mellitus (T1DM)-related CKD barely changed and the age-standardized rates decreased over the years; and the number of deaths and DALYs attributable to type 2 diabetes mellitus (T2DM)-related CKD continuously increased, but the age-standardized rates also decreased. In 2019, 76.03 (58.24-95.61) thousand deaths and 2.13 (1.65–2.67) million DALYs were attributable to diabetes-related CKD, of which, T2DM accounted for 83.32% and 77.0% respectively, and T1DM accounted for the rest. Increasing gender disparity was seen, with males being more heavily impacted. The burden of diabetes-related CKD varied among different age groups, with the numbers of deaths and DALYs attributable to T1DM-related CKD peaking between 45 and 54 years of age and T2DM-related CKD peaking between 75 and 79 years of age; and the crude rates of deaths and DALYs attributable to T1DM-related CKD peaking between 70 and 79 years of age and 40 to 54 years of age, respectively, and T2DM-related CKD peaking over 90 years of age. Among neighboring and G20 countries, the burden of diabetes-related CKD in China was relatively controlled reflected by the ranking of adjusted death and DALYs rates. Conclusions The burden of diabetes-related CKD in China worsens and shows gender disparities and different age distribution. Greater efforts are needed to improve the health outcomes of these patients, especially among males.